Islamophobia Among Malaysian non-Muslim Indian Undergraduate Students: A Focus group Study - Siah, Poh Chua; Low, Sew Kim; Mohd Anis, Nurullashkeen; Tan, Soon Aun; Tan, Ting Ying; Nainee, Sarvarubini (Makara Human Behavior Studies in Asia, 2022)
Malaysia is often regarded as a multi-ethnic nation that inherited a few ethnic groups who were taken as homogeneous unions. Still, the rise of Islamophobia in Western countries has increased the same sentiment among Malaysian non-Muslim Indians, with the HIND RAF protest in 2007 demonstrating their deep concern for religious freedom. This study aims to understand the formation of Islamophobia among Malaysian non-Muslim Indians and their perceptions of Islam. This study employed the focus group method to collect data, thematic analysis to analyze data and purposive sampling to recruit 16 non-Muslim Indian undergraduate students. Intergroup contact theory was used as a framework to understand the mechanism for the formation of Islamophobia. Results showed that although participants from public universities have more contact with Muslim classmates than those from private universities, their knowledge and perception of Islam, as well as the levels of their Islamophobia are quite the same. The results suggest that it is important not only to increase contact between Muslims and non-Muslims in Malaysia but also to increase knowledge of each other’s cultures and religions, because increasing contact without knowledge will only further strengthen the existing prejudice. Through increasing contact and knowledge of both Muslims and non-Muslims, it is believed that the Islamophobia among non-Muslims would be reduced, thus increasing harmony among different ethnic groups.